First record of parasitism by Lespesia archippivora (Diptera: Tachinidae) on Gonodonta fulvangula (Lepidoptera: Noctuidae) - Abrego L, Jeancarlos; Santos Murgas, Alonso (ENTOMOTROPICA, 2025)
This study reports the parasitism of Gonodonta fulvangula Geyer, 1832 by Lespesia archippivora (Riley, 1871) in Cerro Ancón, Panamá, representing a new host record. Two G. fulvangula larvae were observed infested with eggs from a tachinid fly, one of which was taken to the laboratory for further observation. The identification conclusively confirmed that the adults were L. archippivora